Pendidikan Perempuan Perspektif Quraish Shihab Dalam Tafsir al Misbah - Dhomirotul Firdaus; Zaenal Arifin (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2018)
The focus of this article is to discuss how the conception of a woman's position according to M. Quraish Shihab in his book